Incorporation of Nanoalumina Improves Mechanical Properties and Osteogenesis of Hydroxyapatite Bioceramics - Tavassoli, Hossein; Javadpour, Jafar; Taheri, Mahdiar; Mehrjou, Morteza; Koushki, Newsha; Arianpour, Farzin; Majidi, Mohammad; Izadi-Mobarakeh, Jalal; Negahdari, Babak; Chan, Peggy; Ebrahimi Warkiani, Majid; Bonakdar, Shahin (American Chemical Society (ACS), 2018)
A handful of work focused on improving the intrinsic low mechanical properties of hydroxyapatite (HA) by various reinforcing agents. However, the big challenge regarding improving mechanical properties is maintaining bioactivity. To address this issue, we report fabrication of apatite-based composites by incorporation of alumina nanoparticles (n-Al2O3). Although numerous studies have used micron or submicron alumina for reinforcing hydroxyapatite, only few reports are available about the use of n-Al2O3. In this study, spark plasma sintering (SPS) method was utilized to develop HA-nAl2O3 dense bodies. Compared to the conventional sintering, decomposition of HA and formation of calcium aluminates phases are restricted using SPS. Moreover, n-Al2O3 acts as a bioactive agent while its conventional form is an inert bioceramics. The addition of n-Al2O3 resulted in 40% improvement in hardness along with a 110% increase in fracture toughness, while attaining nearly full dense bodies. The in vitro characterization of nanocomposite demonstrated improved bone-specific cell function markers as evidenced by cell attachment and proliferation, alkaline phosphatase activity, calcium and collagen detection and nitric oxide production. Specifically, gene expression analysis demonstrated that introduction of n-Al2O3 in HA matrix resulted in accelerated osteogenic differentiation of osteoblast and mesenchymal stem cells, as expression of Runx-2 and OSP showed 2.5 and 19.6 fold increase after 2 weeks (p < 0.05). Moreover, protein adsorption analysis showed enhanced adsorption of plasma proteins to HA-nAl2O3 sample compared to HA. These findings suggest that HA-nAl2O3 could be a prospective candidate for orthopedic applications due to its improved mechanical and osteogenic properties.
Keywords: 3. Good health